Pengaruh Brand Image Dan Kualitas Layanan Terhadap Keputusan Penggunaan E – Wallet Dana Pada Mahasiswa Universitas Andalas Kampus Payakumbuh - Desri, Syuryatman; Amalia, Renada; Setiawan, Myko Hadi; Hanif, Fadhlan (Sekolah Tinggi Ilmu Ekonomi Surakarta, 2023)
This research was conducted to determine the influence of brand image and service quality on the use of DANA e-wallet among students at Andalas University, Payakumbuh Campus. The method used in this research is a quantitative analysis method. The data used is primary data collected through questionnaires. To measure the magnitude of the influence of these variables, validity tests, reliability tests of regression equations, coefficients of determination, validity tests and reliability tests are used with the help of the SPSS computer application program. Based on the results of data analysis using statistical methods, namely the results of validity tests, reliability tests with valid and reliable results. , The correlation between brand image and usage decisions is 0.486 and the service quality variable on purchasing decisions is 0.544. So, service quality has a strong relationship. From the results of the Analytical Regression, the equation obtained is: Y=12.215+0.491+0.206X, where Y = Usage Decision, and X1= Brand Image, X2 = service quality. From the calculation results of the regression equation test regarding the influence of brand image and service quality on the decision to use the DANA e-wallet, there is a positive or direct relationship between service quality influencing the decision to use.